THE IMPORTANCE OF A NEIGHBORHOOD SOCIAL WORKER IN THE SOCIALIZATION OF CHILDREN FROM AT-RISK FAMILIES IN SECONDARY SCHOOLS (Scientific journal of the Fergana State University, 2024)
This article, based on theoretical and sociological research data, analyzes the concepts of socialization, the risk group of a family and its children. The article also presents the results of an empirical study of cooperation between teachers and community social workers in working with children from at-risk families in secondary schools. Children from families at risk, on the one hand, receive education, upbringing and socialization in educational institutions, on the other hand, they are supported by social protection institutions, a local social worker, the full cooperation of two social entities is very important. give. The article was conducted using a specially designed research questionnaire, which identified the features of interaction between teachers and social workers in the microdistrict.